English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-04-11 07:08:57 · 5 answers · asked by Patrick F 1 in Science & Mathematics Mathematics

5 answers

5(x+3)(x-3)
2(7t-3)(7t+3)

2007-04-11 07:11:04 · answer #1 · answered by Anonymous · 1 0

use the difference of squares formula:
a^2 - b^2 = (a + b)(a - b)

5x^2 - 45
= 5(x^2 - 9)
= 5(x + 3)(x - 3)

98t^2 - 18
= 2(49t^2 - 9)
= 2(7t + 3)(7t - 3)

ab^2 - a^2 - b
I don't see a way to factor this...

2007-04-11 14:15:57 · answer #2 · answered by Mathematica 7 · 0 2

5x²-45 =
x² = 45/5x² = 9
x = \/9
x = 3 or -3
<>
98t²-18 =
t² = 18/98
t = \/9/49
t = 3/7 or - 3/7
<>
ab²-a²-b
a(b² - a) - b
>v<

2007-04-11 14:33:37 · answer #3 · answered by aeiou 7 · 0 0

5(x-3)(x+3)

2(7t-3)(7t+3)

-(-ab^2+a^2+b)

2007-04-11 14:20:10 · answer #4 · answered by Pam 5 · 0 0

5(x^2-9)
5(x-3)(x+3)

2(49t^2-9)
2(7t-3)(7t+3)

a(b^2-a)-b

2007-04-11 14:56:29 · answer #5 · answered by Dave aka Spider Monkey 7 · 0 0

fedest.com, questions and answers